2007
DOI: 10.1007/s10571-007-9198-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced [3H] Glutamate Binding in the Cerebellum of Insulin-Induced Hypoglycaemic and Streptozotocin-Induced Diabetic Rats

Abstract: Our studies demonstrated the increased enzyme activity in the hypoglycaemic rats with increased production of extracellular glutamate. The present study also revealed increased binding parameters of glutamate receptors reflecting an increased receptor number with increase in the affinity. This increased number of receptors and the increased glutamate production will lead to glutamate excitotoxicity and neuronal degeneration which has an impact on the cognitive and memory ability. This has immense clinical sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…In our earlier studies, we reported the glutamate mediated excitotoxicity in the cerebellum of insulin induced hypoglycemic and streptozotocin induced diabetic rats [32]. In the present study, we have demonstrated the role of cholinergic receptors during recurrent hypoglycemia in diabetic rats.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In our earlier studies, we reported the glutamate mediated excitotoxicity in the cerebellum of insulin induced hypoglycemic and streptozotocin induced diabetic rats [32]. In the present study, we have demonstrated the role of cholinergic receptors during recurrent hypoglycemia in diabetic rats.…”
Section: Discussionsupporting
confidence: 68%
“…In a case of episodic bilateral cerebellar dysfunction caused by hypoglycemia, quantitative dynamic PET study demonstrated decreased glucose uptake-to-utilization ratio and increased leak of glucose in the cerebellum indicating that cerebellum is not invariably resistant to hypoglycemia [31]. Studies from our laboratory have demonstrated that cerebellum is susceptible to hypoglycemia [32,33]. Studies on damages of the central nervous system under conditions of hypoglycemia are very important for clinical medicine.…”
Section: Introductionmentioning
confidence: 99%